How Does Intellectual Capital Influence Intention to Start a Digital Innovation Business in Indonesia? - Herlina Herlina (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2025)
This study aimed to identify the intellectual capital (IC) influencing university students in pursuing digital innovation businesses. This study is urgent due to the lack of research on intellectual capital (IC) in Indonesia. Despite having sufficient background knowledge and education, the younger generation predominantly aims to become employees rather than entrepreneurs. This research involved a sample of 312 students from nine universities in Indonesia. The research employed a quantitative approach, utilizing data analysis, namely the Structural Equation Model (SEM). The results indicate that the components of intellectual capital, specifically knowledge and skills, the ability to recognize opportunities, and networks, exert a significant and positive influence on the creation of new digital businesses. The variable level of education exerts no influence. Students are expected to demonstrate improvement. This study recommends government action to enhance development, training, promotion, and communication with current entrepreneurs. Future research should focus on IC studies, particularly in other developing countries.